1988
DOI: 10.1139/v88-167
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the shell structure of atoms and ions as revealed by the one-electron potential,

Abstract: . 66, 1005 (1988).The one-electron potential, v 2 G ( r ) / 2 g P ( r ) , appearing in the Schrodinger equation for the charge density is calculated for the neutral atoms from hydrogen to uranium, and the singly positive ions, from helium to barium and lutetium to radium. These computations, utilizing the nonrelativistic SCF wavefunctions of Cle~nenti and Roetti and McLean and McLean, were performed in order to investigate the concept of shell structure as defined by this potential. v2%$(r)/2*(r) exhibits a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…This means that the topology of s recovers all AIM critical points, but also those related to shells 7 (like the One Electron Potential or OEP 10,11 ) and to very weak interactions (for which ∇ 2 ρ( r) >0). The latter cases are usually related to very weak intramolecular interactions, where the balance between geometric constrains and the weak interaction leads to an absence of critical point.…”
Section: B Local Analysis: Nci Critical Pointsmentioning
confidence: 87%
“…This means that the topology of s recovers all AIM critical points, but also those related to shells 7 (like the One Electron Potential or OEP 10,11 ) and to very weak interactions (for which ∇ 2 ρ( r) >0). The latter cases are usually related to very weak intramolecular interactions, where the balance between geometric constrains and the weak interaction leads to an absence of critical point.…”
Section: B Local Analysis: Nci Critical Pointsmentioning
confidence: 87%
“…It probably started with Bartell and Brockway [1], who reported peaks in the radial charge density. Different functions have been used since then in order to resolve, at least partially, the shell structure of atoms in position space [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The topological properties of the OEP for atoms were extensively analyzed by Sagar et al 13. Using the idea of classically allowed and forbidden regions, where an atomic shell may be defined as successive negative and positive OEP intervals (this definition is somewhat more restrictive than the one adopted in the present study, not allowing for shells solely located in classically forbidden regions), they concluded that the odd‐numbered OEP zeros are best suitable to indicate the atomic shells.…”
Section: Introductionmentioning
confidence: 89%
“…The picture of atomic shells successively filled up by electrons is not reflected by this simple distribution. Recently, the analysis of some specific properties derived from the electron density revealed, at least partially, the atomic shell structure 4–10, 12–16. However, only the average local electrostatic potential 17 and the electron localization function (ELF) 18, 19, as well as ELF modified by the incorporation of the electrostatic potential 20 were able not only to resolve the atomic shell structure, but also to yield reasonable electron numbers for the shell occupations.…”
Section: Introductionmentioning
confidence: 99%